PENGARUH KUALITAS KEHIDUPAN KERJA, BUDAYA ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA PADA SEKRETARIAT BAWASLU PROVINSI SULAWESI TENGGARA - Nirmayanti Nirmayanti; Hayat Yusuf; La Ode Asfahyadin Aliddin; Putu Sumarniwati (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to examine and explain the effect of quality of work life, organizational culture, transformational leadership and motivation on performance. The population in this study is all employees at 3 Secretariat offices in the Bawaslu of Southeast Sulawesi Province as many as 72 people. The sample in this study took all the population as a sample, which amounted to 72 people. The analysis used in inferential statistics is Multivariate Linear Regression performed with the help of SPSS 21.The results of this study indicate that Quality of work life has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, transformational leadership has a positive effect on employee performance, motivation has an effect on employee performance. Finally, Employee growth and development, team orientation, Intellectual Stimulation and the need to achieve employee performance are very able to increase the potential ability of employees to complete work and give confidence to their subordinates and the encouragement to excel and achieve has a good influence in improving employee performance